A Preliminary Study of the Cycling Kinematics Before and After Dimensional Adjustments - Miguel Andrés, I.; Mayagoitia Vázquez, J. J.; Ortiz Lango, L. A.; García Valadez, J. C. (Memorias del Congreso Nacional de Ingeniería Biomédica, 2020)
Cycling has become one of the most popular sports in the world in recent years. But its growing popularity has also resulted in an increasing number of injuries and the subsequent need to better understand the relationship between bicycle dimensions, forces, and the athlete’s anthropometry. The objective of this research was to evaluate the kinematics of the cycling before and after making some adjustments in the dimensions of the bicycle. One healthy subject participated in the study, the kinematics was measured with seven infrared cameras (vicon) and reflective markers. The results found in the study show that there was an increment in the range of motion of the knee and hip joints after the adjustment of the dimensions of the bicycle. The mean range of motion of the left knee was 65.3 and 70.3 degrees before and after the adjustments respectively. For the right knee, it was 68.1 and 74.8 degrees before and after the adjustments respectively. Moreover, it was found an irregular pattern in the range of motion of the ankle joint before making the adjustment to the bicycle. The main contribution of this work is the development of a protocol to measure the range of motion of the knee, hip and ankle joint. This will help to identify irregular patterns in the range of motion and prevent injuries in the athletes.